TPL2 kinase activity is required for Il1b transcription during LPS priming but dispensable for NLRP3 inflammasome activation - Fahey, Denise L.; Patel, Niki; Watford, Wendy T. (Frontiers in Immunology, 2025)
The NLRP3 inflammasome complex is an important mechanism for regulating the release of pro-inflammatory cytokines, IL-1β and IL-18, in response to harmful pathogens. Overproduction of pro-inflammatory cytokines has been linked to cryopyrin-associated periodic syndrome, arthritis, and other inflammatory conditions. It has been previously shown that tumor progression locus 2, a serine-threonine kinase, promotes IL-1β synthesis in response to LPS stimulation; however, whether TPL2 kinase activity is required during inflammasome priming to promote Il1b mRNA transcription and/or during inflammasome activation for IL-1β secretion remained unknown. In addition, whether elevated type I interferons, a consequence of either Tpl2 genetic ablation or inhibition of TPL2 kinase activity, decreases IL-1β expression or inflammasome function has not been explored. Using LPS-stimulated primary murine bone marrow-derived macrophages, we determined that TPL2 kinase activity is required for transcription of Il1b, but not Nlrp3, Il18, caspase-1 (Casp1), or gasdermin-D (Gsdmd) during inflammasome priming. Both Casp1 and Gsdmd mRNA synthesis decreased in the absence of type I interferon signaling, evidence of crosstalk between type I interferons and the inflammasome. Our results demonstrate that TPL2 kinase activity is differentially required for the expression of inflammasome precursor cytokines and components but is dispensable for inflammasome activation. These data provide the foundation for the further exploration of TPL2 kinase inhibitor as a potential therapeutic in inflammatory diseases.